Pusat Kesejahteraan Sosial (PUSKESOS) Griya Sejahtera dan Program Penanganan Covid-19 di Kelurahan Sumber Kecamatan Sumber Kabupaten Cirebon - Nurlaili Khikmawati (Empower : Jurnal Pengembangan Masyarakat Islam, 2022)
The outbreak of Covid-19 cases in various countries, including Indonesia, has had a major impact on the economic condition of the community. In Indonesia, the government is collaborating with various parties in preventing the spread of Covid-19 and handling the economic problems it causes. One of the parties that has an important role in the Covid-19 prevention program and handling economic problems in Indonesia is the Puskesos. Puskesos or Pusat Kesejahteraan Sosial have the function of helping the community to obtain services in order to supply their needs in order to achieve prosperity. Puskesos have a strategic role in the context of equitable distribution of social welfare services for the community, especially the poor affected by covid 19. Given the importance of the role of Puskesos in handling poverty in communities affected by Covid-19, this study aims to examine the role of the Puskesos Griya Sejahtera in the Covid-19 handling program in Sumber Village, Sumber Subdistrict, Cirebon Regency. This research was conducted with a qualitative method with data collected based on observations, interviews and documentation. The results of the study show that several roles of Puskesos in handling covid 19 in the Sumber villages are tracing, collecting data on people affected by Covid-19, collecting data on recipients of social assistance from the government, making certificates of underprivileged people, archiving data, and distributing aid provided by the government. In its implementation, Puskesos Griya Sejahtera encountered several obstacles including the limited number of members and administrators of the puskesos, the lack of socialization about puskesos to the community and the limited infrastructure of puskesos in supporting the work program.